2018
DOI: 10.1161/jaha.118.009351
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Detection Using a Novel Cardiac Ambulatory Monitor Based on Photo‐Plethysmography at the Wrist

Abstract: BackgroundLong‐term continuous cardiac monitoring would aid in the early diagnosis and management of atrial fibrillation (AF). This study examined the accuracy of a novel approach for AF detection using photo‐plethysmography signals measured from a wrist‐based wearable device.Methods and Results ECG and contemporaneous pulse data were collected from 2 cohorts of AF patients: AF patients (n=20) undergoing electrical cardioversion (ECV) and AF patients (n=40) that were prescribed for 24 hours ECG Holter in outpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 46 publications
3
72
0
1
Order By: Relevance
“…With and without the Markov model, the specificities were 95, 89, 92, and 88%, respectively. As a result, the AI algorithm improved the specifications, comparable with the Food and Drug Administration-approved ECG-based Alive-Cor automated AF detector [159].…”
Section: Clinical Trials and Home Use Of Cardiac Monitorsmentioning
confidence: 85%
See 1 more Smart Citation
“…With and without the Markov model, the specificities were 95, 89, 92, and 88%, respectively. As a result, the AI algorithm improved the specifications, comparable with the Food and Drug Administration-approved ECG-based Alive-Cor automated AF detector [159].…”
Section: Clinical Trials and Home Use Of Cardiac Monitorsmentioning
confidence: 85%
“…Measurement of the HR during rest and exercise by most wrist monitors is highly accurate [144,157]. HR monitoring would be valuable to ensure that AF patients are adequately rate-controlled, to mitigate symptoms and decompensation [158,159]. These technologies show promise for long-term noninvasive monitoring of AF.…”
Section: Clinical Trials and Home Use Of Cardiac Monitorsmentioning
confidence: 99%
“…Indeed, we have shown that detecting PAC/PVC can lead to significant false positive reduction during AF detection [ 40 ]. Other recent published reports [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] have largely focused on AF without accounting for PAC/PVC and consequently their accuracy of AF detection was suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…[3] There has been recent interest in the use of consumer devices for the detection of arrhythmias including AF. [5,6] Wrist-worn heart-rate sensors that measure heart rate using Light Emitting Diodes (LEDs) have become increasingly popular but their accuracy has been questioned and some manufacturers advise the heart rate measurement should be considered an estimate and suggest using a chest heart rate sensor for increased accuracy.…”
Section: Introductionmentioning
confidence: 99%